2016
DOI: 10.1038/srep32715
|View full text |Cite
|
Sign up to set email alerts
|

A Molecularly Complete Planar Bacterial Outer Membrane Platform

Abstract: The bacterial outer membrane (OM) is a barrier containing membrane proteins and liposaccharides that fulfill crucial functions for Gram-negative bacteria. With the advent of drug-resistant bacteria, it is necessary to understand the functional role of this membrane and its constituents to enable novel drug designs. Here we report a simple method to form an OM-like supported bilayer (OM-SB), which incorporates native lipids and membrane proteins of gram-negative bacteria from outer membrane vesicles (OMVs). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 62 publications
7
90
0
Order By: Relevance
“…The result is consistent with previous studies, which showed at least ∼2 mM of Ca 2+ is necessary for the formation of PLE-SLB on SiO 2 /Si, mica, TiO 2 , indium tin oxide and gold (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). In the previous studies of the bacterial mimic lipid bilayer, however, averaged response from the sample was mainly obtained using QCM and fluorescence microscopy (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). The results in this study showed the heterogeneity of SLB especially at the threshold [Ca 2+ ] around 2.5 mM.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The result is consistent with previous studies, which showed at least ∼2 mM of Ca 2+ is necessary for the formation of PLE-SLB on SiO 2 /Si, mica, TiO 2 , indium tin oxide and gold (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). In the previous studies of the bacterial mimic lipid bilayer, however, averaged response from the sample was mainly obtained using QCM and fluorescence microscopy (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). The results in this study showed the heterogeneity of SLB especially at the threshold [Ca 2+ ] around 2.5 mM.…”
Section: Resultssupporting
confidence: 93%
“…As a bacterial model cell system, reconstituted Escherichia coli (E. coli) cell membrane has been studied (Dodd et al, 2008;Merz et al, 2008;Lopes et al, 2010;Unsay et al, 2013;Lind et al, 2015;Phan and Shin, 2015;Hsia et al, 2016;Konarzewska et al, 2017;Márquez and Vélez, 2017). Understanding the bacterial membrane system helps in revealing the mechanism of molecular recognition and material transportation during bacterial infection for medical technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent progresses in the development of supported asymmetric bilayers made OM models amenable to characterization via structural techniques. [18][19][20] The first MD simulation of a bacterial outer membrane was performed for the rough LPS of Pseudomonas aeruginosa using the GLYCAM93 21 and AMBER95 22 atomic parameters to describe carbohydrate and lipid moieties, respectively. 23 The simulated bilayer consisted of 16 LPS units in the outer leaflet, 40 DPPE (1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine) units in the inner leaflet and a total of 104 Ca 2+ to neutralize the system.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, polymyxins bind to lipids in the bacterial membrane via electrostatic interactions. Hydrophobic interactions between their N ‐terminal fatty acid tail and the membrane fatty acid lipid tails lead to insertion, membrane destabilization, and cell lysis . Electrostatic interactions are responsible for the initial binding of the antibacterial compound to the anionic surface of the bacteria.…”
mentioning
confidence: 99%